2010
DOI: 10.1159/000314995
|View full text |Cite
|
Sign up to set email alerts
|

Modest but Increased Penetration through Damaged Skin: An Overview of the in vivo Human Model

Abstract: Background/Aim: Quantifying percutaneous penetration of topical drugs as well as those compounds relevant to occupational exposure is important for assessing their delivery, efficacy and toxicology. Methods for assessing penetration are established for intact skin; however, what may be equally relevant is how much penetration occurs through damaged skin. Methods: The Embase database was accessed online in March 2009 in search of human in vivo studies measuring penetration through damaged or diseased skin. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 79 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…Using acetone-disrupted hairless mouse skin as a model membrane, the authors showed that both hydrophilic and amphipathic compounds, including sucrose, caffeine and hydrocortisone, had increased permeability in vitro. These findings coincide with the conventional understanding that hydrophilic molecules have the greatest enhancement of penetration under conditions of physical or chemical insult (84).…”
Section: Skin Health and Integritysupporting
confidence: 88%
“…Using acetone-disrupted hairless mouse skin as a model membrane, the authors showed that both hydrophilic and amphipathic compounds, including sucrose, caffeine and hydrocortisone, had increased permeability in vitro. These findings coincide with the conventional understanding that hydrophilic molecules have the greatest enhancement of penetration under conditions of physical or chemical insult (84).…”
Section: Skin Health and Integritysupporting
confidence: 88%
“…Physicochemical properties are important determinants of stripping effects. Gattu and Maibach () review studies comparing such properties and resulting absorption rates.…”
Section: Mechnical Damage: Tape Stripping Abrasionmentioning
confidence: 99%
“…In this regard, it has been acknowledged that MD is not a technique where mass balance can be obtained [34] . Although the in vitro recovery of CP by IL as a perfusate was exceptionally high, the same recovery is not obtained in vivo -in which case a 'wash-out' phenomenon would have had to be expected.…”
Section: In Vivo MD Studymentioning
confidence: 99%